2022
DOI: 10.1177/25151274221108433
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of a Blended Entrepreneurship Course on Secondary Students' Entrepreneurial Self-Efficacy and Entrepreneurial Intentions

Abstract: This mixed-methods study examined the impacts of a blended entrepreneurial course on secondary students’ entrepreneurial self-efficacy (ESE) and intentions, which were measured with pre- and post-surveys. The artifacts students created (elevator pitches and business canvas models) were collected. Survey results revealed no improvement in ESE, but significant improvements in two dimensions of intentions: professional attraction and entrepreneurial capacity. Artifact results showed that students could identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Zhang et al (2014) illustrated a positive correlation between EE and perceived entrepreneurial desirability. Similarly, Hershmann et al (2022) found that curricular activities can increase the desirability of entrepreneurship as a career choice among students. If pupils have experienced entrepreneurial curricular activities, such as participating in the Youth Achievement program, their entrepreneurial desirability is amplified (Peterman and Kennedy, 2003).…”
Section: The Role Of Curricular and Extracurricular Entrepreneurial A...mentioning
confidence: 94%
See 2 more Smart Citations
“…Zhang et al (2014) illustrated a positive correlation between EE and perceived entrepreneurial desirability. Similarly, Hershmann et al (2022) found that curricular activities can increase the desirability of entrepreneurship as a career choice among students. If pupils have experienced entrepreneurial curricular activities, such as participating in the Youth Achievement program, their entrepreneurial desirability is amplified (Peterman and Kennedy, 2003).…”
Section: The Role Of Curricular and Extracurricular Entrepreneurial A...mentioning
confidence: 94%
“…Although changes in ESE before and after curricular activities are not necessarily important (Huber et al, 2014; Morris et al, 2013; Von Graevenitz et al, 2010), previous research has noted that curricular activities and pedagogical choices positively influence students’ perceptions of their entrepreneurial skills and competencies (Birdthistle et al, 2016; Liñán and Chen, 2009) and their ESE (Shinnar et al, 2014; Zhao et al, 2005). However, research in this area is not consistent, as a study by Hershmann et al (2022) showed that some curricular activities may not improve students’ ESE. The common rationale, though, is that exposing students to curricular activities, such as cases, course work, and teaching methods, supports their entrepreneurial self-confidence (Arranz et al, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that students in entrepreneurship education demonstrated a statistically significant increase in entrepreneurial mindset, specifically in communication and collaboration, opportunity recognition, critical thinking, and problem-solving. In another study, Hershmann et al (2023) indicate that some learners could recognise issues and produce solutions but could not forecast income. According to Alakaleek et al (2023), entrepreneurship education improved students' knowledge and behaviour.…”
Section: Evaluation and Assessmentmentioning
confidence: 95%